Go-Khitan's Home Care Circumcision Service Innovation Increases Customer Satisfaction - Sutrisno, Sutrisno; Herawati, Vitri Dyah (Journal of Applied Nursing and Health, 2024)
Background: Innovation has an important role in the implementation of health-related services to the community so that they can be better, cheaper and faster. Home care Go-Khitan is a health service provided by professionals at the patient's place of residence with the aim of helping to meet the patient's needs in overcoming the health problems they are experiencing. This research aims to see the extent of Go-Khitan Home Care health service innovation and its impact on circumcision customer satisfaction Methods: The type of research carried out was descriptive correlative using a cross-sectional design with a sample size of 32 respondents. Data collection was carried out by taking data through innovation questionnaires and customer satisfaction questionnaires directly and by Google forms. Results: The research results were analyzed using the Kendall Tau statistical test and the p value was 0.01. This value have meaning that Go-khitan home care health service innovation has a significant relationship with customer satisfaction Conclusion: Circumcision at home In a roundabout way, innovation will raise the bar for service excellence. Customer satisfaction will rise as service quality reaches its maximum potential.